Brake Drum Temperature Adjustment and The Brake Lining Gap's Impact On Motor Vehicle Brake Efficiency - Novianto, Arief; Turasno, Buang; Ismail, Rifky; Achmaditiya, Galuh (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2024)
Brakes are a key component in motor vehicle systems that play a vital part in decreasing the likelihood of accidents on the road. Improper component adjustment in the brake system, particularly with drum brakes, can cause the brakes to perform inefficiently. This research aimed to determine the effects of significant variations in drum brake and brake lining temperature on motorized vehicle braking efficiency. The brake lining gap size and the drum brake's temperature are controlled in this study's experimental setup. From these various modifications, the main braking efficiency was verified using a brake tester. The brake lining gap is 0.3 mm, 1 mm, and 1.7 mm. Meanwhile, the brake drums' temperatures have been adjusted to 30, 90, and 150 degrees Celsius. The results show that braking efficiency decreases with increasing brake lining gap. The effectiveness of the drum brake decreases as the temperature rises. Meanwhile, the fluctuating brake lining spacing and temperature also affect braking efficiency. The brakes' effectiveness decreases with increasing distance between the drum brake's lining and temperature.